Postmodernity and Late Capitalism: Reading of Anderson and Harvey - Koirala, Saroj (Tribhuvan University Journal, 2016)
This article deals with two pioneer scholars of postmodernism, David Harvey and Perry Anderson. The former disagrees with Jameson’s response to postmodern condition, and the latter concentrates on the economic and geopolitical conditions that have nurtured the idea and changes. However, both of them are aware of the totality of contemporary life. Postmodern condition, for Harvey, is dangerous as it avoids the issues of the realities of political economy and global power. He opines that capitalist response to 1973 economic crisis openly attacked the rigidity of Fordism,which consequently gave birth to the postmodern condition. Harvey perceives postmodernism as people’s aesthetic and cultural response to unprecedented. Though these critics adopt different approaches both agree with the claim that postmodern is encompassing the totality of our life experience. Finally, the article exemplifies how this generalization is working in popular Indian culture particularly focusing on Valentine Day celebration. The role played by Indian media has changed the society and culture which might be similar to Nepalese context. Thus, postmodern condition elaborated by Harvey and Anderson are not delimited to the first world but also seem relevant in the so called third world.